Analysis of Marketing Strategies in Increasing Sales Volume of Palapa Coffee in Bandar Lampung - Rosita, Dinda Ayu; Warganegara, Tri Lestira Putri (LPPPIPublishing, 2024)
The purpose of this study is to test marketing strategies to increase sales volume in Palapa Coffee and understand the strengths, weaknesses, opportunities, and threats in Palapa Coffee and formulate better competitive marketing strategy alternatives using the SWOT analysis method. This study used descriptive research method. This study used data collection techniques with observation, interview, documentary, and literature research methods. Technical data analysis using SWOT analysis with a SWOT matrix model. The results showed that marketing strategies to increase sales volume in terms of price, product, place, and promotion were based on the performance of Palapa Coffee employees. SO, ST, WO, and WT strategies also affect the performance of Palapa Coffee. Based on calculations using SWOT analysis, it can be concluded that Palapa Coffee is in quadrant I position which supports aggressive strategies by using its strengths to take advantage of opportunities. Meanwhile, the results of the IE matrix show that the company is in the position of quadrant I (one), namely Growth oriented strategy. This position signifies his company with its marketing strategy that supports an aggressive strategy on the various opportunities and strengths it has.